Purification of phycocyanin from Spirulina platensis by combination diafiltration/ ultrafiltration membrane - Agustini, Tri Winarni; Anggo, Apri Dwi; Yuliani, Yuliani (Hasanuddin University Food Science and Technology Study Program, 2025)
Phycocyanin, a blue pigment derived from the cyanobacterium Spirulina platensis, is typically purified through either single-step or multi-step processes. The purity of phycocyanin is crucial for its applications as a food colorant, in cosmetics, as a biomarker, and for analytical purposes. In this study, we report the purification of phycocyanin using a multi-step process involving extraction, ammonium sulfate precipitation, and diafiltration/ultrafiltration (DF/UF) with cycle times of 20, 30, and 40 minutes. The aim of this research to determine the effect of DF/UF time on flux, retention rates and purity on phycocyanin purification. The combination of DF/UF allowed the improving the purity of the phycocyanin in the retentate fraction. Sample that have been extracted and ammonium sulphate precipitation, were purified by ultrafiltration membrane using of hydrophilic polyethersulfone (PESH) membrane of 50 kDa MWCO. The DF/UF system was operated at 1.0 ± 0.1 Psi and at 24 ± 1oC. sample were collected during both DF/UF process in order to evaluated flux, retention rates and purity ratio of phycocyanin. The best DF/UF process were operate at 40 min per cycle, with a mean permeate flux 6.89 L/m2h and retention rate 96.99% was found to be optimal. This process resulted in phycocyanin with purity and concentration of 2.54 and 0.30 mg/mL, respectively. Hence, the DF/UF process were operated at 40 min per cycle potential for a biomarker application.